PROFIL ASSESSMENT GURU BIDANG STUDI MATEMATIKA SMP DI KECAMATAN TEMPEH - Hanafi A, Joli; Sunardi, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2014)
Abstract.The research aimed to know the level ofunderstanding ofjunior high school mathematicsteachers for assessment, the developmentassessment and the implementation ofassessment injunior high school mathematicsteachers in Tempeh Subdistrict. The research subject is six junior high school from eight junior high school in Tempeh Subdistrict. The data collection methods used in this research is questionnaire, observation, interview, and documentation. Based on research it shows thatthe level ofunderstanding ofjunior high school mathematicsteachers about assessment in Tempeh Subdistrict as much as 60,17%, 75,00% mathematicsteachershad developedassessment, and 53,91% mathematicsteachershadconducted assessmentin accordance with BSNP. Keywords:assessment, curriculum, mathematicsteachers